Perubahan kondisi biofisik-kimia lahan akibat pembangunan kanal pada areal IUPHHBK-HA (Sagu) PT. Austindo Nusantara Jaya Agri Papua di Kabupaten Sorong Selatan - Reynold Kesaulija; Nurhaida Sinaga; Max J. Tokede (Cassowary, 2018)
The constructions of canals for water use and management as well as supporting activities of productions, transportation and firebreaks lines are expected to have an impact on the biophysical and chemical changes in construction land. Therefore, the aims of this research are to know the amount of vegetation lost due to land clearing for canal constructions, land biophysical-chemical conditions changed as a result of canal clearing, aboveground carbon dioxide estimation and soil carbon stock estimation. Primary data collection determined by purposive on canal line for stand structure and composition, along with soil carbon estimation. The results showed that the opening of canal area of 82,35 ha will result in the loss of 19.866 sago trees on 40 cm average in diameter and 3.642 mature trees. Thus, sago starch on 82,35 ha will lost as much as 637,27 tons or 637.265,48 kg. Changes in land biophysical-chemical due to canal constructions are habitat fragmentation, increase in soil erosion, land slide of canal wall, changes in water quality particularly solid suspension total as a direct impact to increased turbidity, sedimentation, and siltation of canals. Furthermore, the impact of 82,35 ha canal construction was increasing of carbon dioxide (CO2) emission as much as 38.716,48 ton, and it is estimated that it will increase in line with future canal construction. Based on soil bulk density ranging from 0,58 to 1.22 g/cm3 and Carbon-organic content ranging from 16.65 to 54,16 %, it is estimated that carbon stock on 0 to 30 cm soil layer on 1 Ha area will be lost as 109 ton.